IDENTIFICATION OF TASKS AND PROCEDURES NECESSARY FOR ASSESSING PRACTICAL WORK IN BLOCK/BRICKLAYING AND CONCRETING IN TECHNICAL COLLEGES IN NIGER STATE - Tsado N. Ibrahim & Dr. Umar B. Kudu, (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
This study was designed to identify tasks and procedures necessary for assessing practical work in Buck/Block laying and concreting in Technical colleges in Niger state. Two research questions were formulated to guide the study. Two null hypotheses were formulated and tested at the probability of 0.005 level of significance. Twenty-Nine structured questionnaire items were developed and used for the study while three experts were engaged to face-validate the instrument. The instrument was pilot tested on 15 students and the reliability coefficient of the entire instrument was 0.87. Descriptive Survey Research Design was used for study, the respondents for the study were 69 made up of 49 building Technology Teachers, and 20 Registered Builders. The major findings of the study include among others that, some tasks have been identified appropriate for inclusion in the instrument for assessing practical work in Brick/Block laying and concreting in Technical colleges in Niger State. It was recommended that Brick/Block laying and concreting teachers should be acquainted with the developed instrument to enhance the uniform standards in assessing student’s practical work.